Chromosome 11q13 deletion syndrome - Yu-Seon Kim; Gun-Ha Kim; Jung Hye Byeon; So-Hee Eun; Baik-Lin Eun (Korean Pediatric Society, 2016)
Chromosome 11q13 deletion syndrome has been previously reported as either otodental syndrome or oculo-oto-dental syndrome. The otodental syndrome is characterized by dental abnormalities and high-frequency sensorineural hearing loss, and by ocular coloboma in some cases. The underlying genetic defect causing otodental syndrome is a hemizygous microdeletion involving the FGF3 gene on chromosome 11q13.3. Recently, a new form of severe deafness, microtia (small ear) and small teeth, without the appearance of eye abnormalities, was also reported. In this report, we describe a 1-year-old girl presenting with ptosis of the left upper eyelid, right auricular deformity, high-arched palate, delayed dentition, simian line on the right hand, microcephaly, and developmental delay. In this patient, we identified a deletion in the chromosome 11q13.2-q13.3 (2.75 Mb) region by using an array-comparative genomic hybridization analysis. The deletion in chromosome 11q13 results in a syndrome characterized by variable clinical manifestations. Some of these manifestations involve craniofacial dysmorphology and require a functional workup for hearing, ophthalmic examinations, and long-term dental care.